Variance of Physiological Conditioning between Biceps Muscle and Quadratus Femoris Muscle as A Result of Developing Maximum Force - Jassim, Mouyed; Saleh, Hamid (Journal of Physical Education, 2007)
Muscular force trainings contribute in building the muscles and increasing its size and ability to contract. This development is companied by a state of physiological change in the muscle which generally effects the size and the ability of the motor unit after training.The importance of the study comes from showing the effect of developing the maximum force on the physiological conditioning of the biceps muscle and the quadratus femoris muscle.The problem of the study is about the variance of the physiological developments which may provide every muscular group with a significant feature and make its training difficult.The aim of the study is to know the rates of the physiological developments of the muscle and its electric activity (EMG) as a result of developing the maximum force of the biceps muscle and the quadratus femoris muscle.The hypothesis of the study refers to the existence of variance in the physiological developments rates of the muscle and its electric activity (EMG) as a result of developing the maximum force of the biceps muscle and the quadratus femoris muscle.The subject of the study consists of 11 eleven students of the first-year students/ Physical Education College who practice the force trainings as amateur. The subject has been divided into two groups. The first one practices on curl exercise and the second on deep knee exercise according to especially prepared curriculum for developing the maximum muscular force in 8 weeks, 3 training units per a week. Measures of the maximum muscular force of arms and legs and its electric activity (EMG)have been taken, and the study comes out with these conclusions: 1. Legs muscles have achieved a developing rate (22%) more than the rate of the arms rate (18%) asserting a better response and rapid developing ability. 2. As a result of maximum force training, physiological conditionings occur to the electric activity indicators of the muscle (EMG) showing a developing rate (51%) in the contract force indicator (Amp) of the quadratus femoris muscle and (21%) in the biceps muscle whereas the developing rate of the contract duration (Dur) of the quadratus femoris muscle is (21%) and of the biceps muscle is (31%). Accordingly, the study recommends the following : 1. Concern should be given to the muscular force training of the biceps muscle toward extending the duration of the muscular contract through force stamina exercises. 2. Concern should be given to the muscular force training of the quadratus femoris muscle toward increasing the stimulation of the contract force through power exercises.